2020
DOI: 10.1016/j.xplc.2020.100043
|View full text |Cite
|
Sign up to set email alerts
|

Development of Plant Prime-Editing Systems for Precise Genome Editing

Abstract: Prime-editing systems have the capability to perform efficient and precise genome editing in human cells. In this study, we first developed a plant prime editor 2 (pPE2) system and test its activity by generating a targeted mutation on an HPT -ATG reporter in rice. Our results showed that the pPE2 system could induce programmable editing at different genome sites. In transgenic T 0 plants, pPE2-generated mutants occurred with 0%–31.3% frequency, suggesting that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
129
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(134 citation statements)
references
References 60 publications
(59 reference statements)
2
129
0
3
Order By: Relevance
“…Very recently, several reports have shown that prime editing can be applied to cereal plants Lin et al, 2020;Tang et al, 2020;Xu et al, 2020a;Xu et al, 2020b;Butt et al;Hua et al). All these studies showed that the efficiency of PPEs greatly varies between target sites and is sensitive to several parameters such as both the PBS and RT sequence.…”
Section: Resultsmentioning
confidence: 99%
“…Very recently, several reports have shown that prime editing can be applied to cereal plants Lin et al, 2020;Tang et al, 2020;Xu et al, 2020a;Xu et al, 2020b;Butt et al;Hua et al). All these studies showed that the efficiency of PPEs greatly varies between target sites and is sensitive to several parameters such as both the PBS and RT sequence.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a novel and universal precision genome-editing technology named prime editing was developed and tested in mammalian cells [1]. More recently, seven groups reported applications of prime editors (PE) in rice and wheat, and six groups achieved prime-edited rice lines [2][3][4][5][6][7][8]. Excluding the data based on enriching strategies or that are unsuitable for comparison, a total of 164 prime-edited rice lines transformed with 39 prime editors targeting 11 endogenous rice genes were generated in these previous reports [2,3,5,6,8].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, seven groups reported applications of prime editors (PE) in rice and wheat, and six groups achieved prime-edited rice lines [2][3][4][5][6][7][8]. Excluding the data based on enriching strategies or that are unsuitable for comparison, a total of 164 prime-edited rice lines transformed with 39 prime editors targeting 11 endogenous rice genes were generated in these previous reports [2,3,5,6,8]. The highest editing efficiencies achieved by the five groups ranged from 2.22% to 31.3% [2,3,5,6,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the SpCas9(H840A) nickase-guided Moloney murine leukemia virus reverse transcriptase (M-MLV RT) has been developed in both rice and wheat, facilitating the introduction of all 12 base-to-base conversions, small insertion as well as deletions in a precise and targeted manner through reverse transcription of the pegRNA [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%